CHILE'S STUDENT PROTESTERS - Padgett, By Tim (La Sociología en sus Escenarios, 2012)
<!--[if gte mso 9]> Normal 0 21 false false false ES-CO X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]--> Resumen.Tim Padget señala que Chile pese a sus éxitos económicos muestra uno de los primeros lugares mundiales en desigualdad social. Esto es producto de un modelo económico neoliberal extremista. Sin embargo, las grandes manifestaciones sociales (ecológicas y estudiantiles) han mostrado un país inconforme y una violenta represión policial a los estudiantes que exigen cambios estructurales en la sociedad chilena. Abstract.Billionaire President Sebastián Piñera was riding as high as the Andes when 2011 began and enjoyed a 63% approval rating. Chile widely touted as Latin America's most developed nation, but festering behind the fortunate façade were long unaddressed issues of inequality that belied Chile's First World status. The real hot button, however, was- and during Chile's southern hemisphere winter, students took to the streets en masse to force Piñera to address their grievances about access to quality education. Led by a charismatic 23-year-old, left-wing undergraduate, Camila Vallejo, the uprising, has grown into a broader demand for structural change in Chile. It has also sent the rightist Piñera's approval rating plunging as low as 27% (currently 31%), while as many as 79% (currently 67%) of Chileans have said they back the student protesters.